Time to differentiate postactivation "potentiation" from "performance enhancement" in the strength and conditioning community - Prieske, O.; Behrens, M.; Chaabene, H.; Granacher, U.; Maffiuletti, N. A. (Sports Medicine, 2020)
Coaches and athletes in elite sports are constantly seeking to use innovative and advanced training strategies to efficiently improve strength/power performance in already highly-trained individuals. In this regard, high-intensity conditioning contractions have become a popular means to induce acute improvements primarily in muscle contractile properties, which are supposed to translate to subsequent power performances. This performance-enhancing physiological mechanism has previously been called postactivation potentiation (PAP). However, in contrast to the traditional mechanistic understanding of PAP that is based on electrically-evoked twitch properties, an increasing number of studies used the term PAP while referring to acute performance enhancements, even if physiological measures of PAP were not directly assessed. In this current opinion article, we compare the two main approaches (i.e., mechanistic vs. performance) used in the literature to describe PAP effects. We additionally discuss potential misconceptions in the general use of the term PAP. Studies showed that mechanistic and performance-related PAP approaches have different characteristics in terms of the applied research field (basic vs. applied), effective conditioning contractions (e.g., stimulated vs. voluntary), verification (lab-based vs. field tests), effects (twitch peak force vs. maximal voluntary strength), occurrence (consistent vs. inconsistent), and time course (largest effect immediately after vs. ~ 7 min after the conditioning contraction). Moreover, cross-sectional studies revealed inconsistent and trivial-to-large-sized associations between selected measures of mechanistic (e.g., twitch peak force) vs. performance-related PAP approaches (e.g., jump height). In an attempt to avoid misconceptions related to the two different PAP approaches, we propose to use two different terms. Postactivation potentiation should only be used to indicate the increase in muscular force/torque production during an electrically-evoked twitch. In contrast, postactivation performance enhancement (PAPE) should be used to refer to the enhancement of measures of maximal strength, power, and speed following conditioning contractions. The implementation of this terminology would help to better differentiate between mechanistic and performance-related PAP approaches. This is important from a physiological point of view, but also when it comes to aggregating findings from PAP studies, e.g., in the form of meta-analyses, and translating these findings to the field of strength and conditioning.